Arctic sea ice associated biodiversity: importance and challenges. - Barry, Tom (Arctic Portal, 2011)
Mr. Tom Barry, CAFF – Conservation of Arctic Flora and Fauna, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.